IMPLEMENTASI ENERGI BIOMASSA DALAM BENTUK PENYEBARAN LUBANG RESAPAN BIOPORI DI FAKULTAS HUKUM UNIVERSITAS KRISNADWIPAYANA - Christine Widyastuti; Isworo Pujotomo; Muchammad Nur Qosim; Rinna Hariyati; Aas Wasri Hasanah; Tony Koerniawan; Oktaria Handayani (Sekolah Tinggi Teknik - PLN, 2019)
One area prone to the impact of the rainy season which later becomes an area prone to flooding is certainly an area that is densely populated and does not have sufficient water drainage. Where land that could have become water absorption land is actually covered by buildings. To overcome this problem, one of the solutions is to make water infiltration holes back even on narrow land. In holes that are 10 cm in diameter and 80 cm - 100 cm deep, organic waste in the form of dried leaves or household waste can be inserted. (kitchen garbage). This organic waste serves to help the life of earthworms and termites which will later make biopores (pores / small) in the soil. In waterways, this infiltration hole can be made every one meter. And from this biopore infiltration hole, harvest yields can also be taken in the form of organic fertilizer (biomass energy) which has economic value. For this reason, this dissemination was carried out in the Faculty of Law Krisnadwipayana University.